Mark Twain’s Cat: Investment experience, categorical thinking, and stock selection - Huang, Xing (Journal of Financial Economics, 2019)
This paper examines the effect of prior investment experience in specific industries on subsequent investment decisions. Using households’ trading records from a large discount broker between 1991 and 1996, I find that prior success in a given industry increases the likelihood of subsequent purchases in the same industry. The effect is stronger for more recent experiences and for less sophisticated or diversified investors, and it is not wealth enhancing. The results suggest investors categorize industries at a highly resolved level, finer than the Fama–French ten-industry classification. Similar effects are also apparent for size- and value-based categories but at smaller magnitudes.